Feminism, capitalism, and ecology - Oksala, Johanna, 1966- (Northwestern University Press, 2023)
"A philosophical work that exposes the systemic logic by which environmental destruction and gender oppression are jointly rooted in capitalism, establishing the theoretical foundations on which an effective political alliance can be built today"--